Diabetes mellitus Type II and cognitive capacity in healthy aging, mild cognitive impairment and Alzheimer's disease. (30th June 2016) - Degen, Christina; Toro, Pablo; Schönknecht, Peter; Sattler, Christine; Schröder, Johannes
Abstract: While diabetes mellitus (DM) Type II has repeatedly been linked to Alzheimer´s disease (AD) and mild cognitive impairment (MCI), longitudinal research is scarce and disease duration has not always been taken into account. In a birth cohort born between 1930 and 1932 we investigated the influence of DM Type II and disease duration on neuropsychological functioning (memory/learning, attention, verbal fluency, visuospatial thinking and abstract thinking) across 14 years. Subjects who developed MCI or AD performed significantly poorer on all neuropsychological tests applied. While significant main effects DM Type II did not arise, its presence led to a significant deterioration of performance in the digit symbol test and visuospatial thinking over time. Additionally, in visuospatial thinking this change was more pronounced for individuals suffering from MCI/AD. We found that, as a concomitant disease DM Type II does not affect memory functioning, which is typically compromised in MCI and early AD. Rather, it may lead to deficits in cognitive flexibility and visuospatial thinking. DM Type II can be considered a frequent comorbid condition which can aggravate the course of MCI and AD. In this respect it may serve as a model for other comorbid conditions in AD.